ANALYSIS OF COMPLEX CHROMOSOMAL ABNORMALITIES IN A CASE OF MULTIPLE MYELOMA USING SPECTRAL KARYOTYPING - Govindasamy, Perumal; Kulshreshtha, Pooja S; Pandurangan, Prabu; Tarigopula, Anil; Kadandale, Jayarama S; Samuel, Chandra R (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: It was proposed to determine the chromosomal abnormalities in a 49-year-old male patient with multiple myeloma (MM) employing both conventional and advanced molecular cytogenetic techniques. Methods: GTG-banding and spectral karyotyping (SKY) on fixed metaphases obtained from LPS-stimulated bone marrow cells and interphase fluorescence in situ hybridization (iFISH) on unsorted marrow cells were carried out to identify genetic markers of prognostic significance. Results: The abnormal chromosomes observed through conventional cytogenetics could be resolved with SKY technique. The translocation t(4;14) (p16;q32) indicating FGFR3/IGH fusion and deletion of 13q14.3 was noticed using iFISH. The genetic abnormalities confirmed a poor prognostic outcome in the patient who died within 6 months of diagnosis. Conclusion: This report emphasizes the need for multicolor FISH techniques besides iFISH to resolve complex abnormalities and to identify cryptic aberrations of importance in risk stratification of MM patients.